A review of self-healing hydrogels for bone repair and regeneration: Materials, mechanisms, and applications - Li, Bo; Li, Chenchen; Yan, Ziyi; Yang, Xiaoling; Xiao, Wenqian; Zhang, Dawei; Liu, Zhongning; Liao, Xiaoling (International journal of biological macromolecules, 2025)
Bone defects, which arise from various factors such as trauma, tumor resection, and infection, present a significant clinical challenge. There is an urgent need to develop new biomaterials capable of repairing a wide array of damage and defects in bone tissue. Self-healing hydrogels, a groundbreaking advancement in the field of biomaterials, displaying remarkable ability to regenerate damaged connections after partial severing, thus offering a promising solution for bone defect repair. This review first presents a comprehensive overview of the progress made in the design and preparation of these hydrogels, focusing on the self-healing mechanisms based on physical non-covalent interactions and dynamic chemical covalent bonds. Subsequently, the applications of self-healing hydrogels including natural polymers, synthetic polymers, and nano-hybrid materials, are discussed in detail, emphasizing their mechanisms in promoting bone tissue regeneration. Finally, the review addresses current challenges as well as future prospects for the use of hydrogels in bone repair and regeneration, identifying osteogenic properties, mechanical performance, and long-term biocompatibility as key areas for further improvement. In summary, this paper provides an in-depth analysis of recent advances in self-healing hydrogels for bone repair and regeneration, underscoring their immense potential for clinical application.